Identifying health and healthcare priorities in rural areas: A concept mapping study informed by consumers, health professionals and researchers - Anna Wong Shee; Alex Donaldson; Renee P. Clapham; John C. Aitken; Jaithri Ananthapavan; Anna Ugalde; Vincent L. Versace; Kevin Mc Namara (BMC, 2024)
Abstract Background It is vital that health service delivery and health interventions address patients' needs or preferences, are relevant for practice and can be implemented. Involving those who will use or deliver healthcare in priority-setting can lead to health service delivery and research that is more meaningful and impactful. This is particularly crucial in rural communities, where limited resources and disparities in healthcare and health outcomes are often more pronounced. The aim of this study was to determine the health and healthcare priorities in rural communities using a region-wide community engagement approach. Methods This multi-methods study was conducted in five rural communities in the Grampians region, Western Victoria, Australia. It involved six concept mapping steps: (1) preparation, (2) generation (brainstorming statements and identifying rating criteria), (3) structuring statements (sorting and rating statements), (4) representation of statements, (5) interpretation of the concept map and (6) utilization. Community forums, surveys and stakeholder consultations with community members and health professionals were used in Step 2. An innovative online group concept mapping platform, involving consumers, health professionals and researchers was used in Step 3. Results Overall, 117 community members and 70 health professionals identified 400 health and healthcare issues. Six stakeholder consultation sessions (with 16 community members and 16 health professionals) identified three key values for prioritizing health issues: equal access for equal need, effectiveness and impact (number of people affected). Actionable priorities for healthcare delivery were largely related to access issues, such as the challenges navigating the healthcare system, particularly for people with mental health issues; the lack of sufficient general practitioners and other health providers; the high travel costs; and poor internet coverage often impacting technology-based interventions for people in rural areas. Conclusions This study identified actionable health and healthcare priorities from the perspective of healthcare service users and providers in rural communities in Western Victoria. Issues related to access, such as the inequities in healthcare costs, the perceived lack of quality and availability of services, particularly in mental health and disability, were identified as priorities. These insights can guide future research, policy-making and resource allocation efforts to improve healthcare access, quality and equity in rural communities.